The Effect of Store Atmosphere and Consumer Satisfaction on The Consumer Repurchase Intention of Social Media Cafe J.City Medan - T Teviana (Outline Publisher, 2022)
This study aims to determine the Effect of Store Atmosphere and Consumer Satisfaction on Consumer Repurchase Interests of Sosmed Cafe J.City Medan. This research uses quantitative methods with a sampling technique using purposive sampling technique, with a total sample of 100 people who have visited Sosmed Cafe J. City of Medan. Partially Store Atmosphere and Consumer Satisfaction have a positive and significant effect on consumer repurchase intention of Sosmed Cafe J.City Medan. Based on the results of the study, it shows that the Store Atmosphere and Consumer Satisfaction variables simultaneously influence Repurchase Intention. The coefficient of determination test shows a value of 0.522 which means that Store Atmosphere and Consumer Satisfaction have an effect on Repurchase Interest of 52.2% while the rest is influenced by another variable